Pengaruh Penambahan Tepung Kacang Hijau dan Gliseril Monostearat Pada Tepung Jagung Terhadap Sifat Fisik dan Organoleptis Roti Tawar yang Dihasilkan - Rob Mudjisihono; S. Joni Munarso; Zuheid Noor (agriTECH, 1993)
An experiment was conducted to evaluate the effect of addition of mungbean flour and gliceryl monostearat (GMS) on the loaf volume, hardness, porosity, colour, texture, taste and flavour of bread. Corn and mung bean flour and then added with 1, 2 and 3 percents of GMS. Physical analysis showed that corn and mungbean flour can be used to produce a good quality bread. Addition of fifteen percents of mungbean in flour resulted in a good loaf volume and increase in the hardness of bread. Addition of GMS with several concentrations were also not negatively affecting to the taste, flavour, the texture and the colour of bread. The panelist prefered the texture of bread with addition of five percents mungbean flour and Iwo percents GMS. While, the panelist prefer the taste of bread with addition of ten percents mungbean flour and two percents GMS.